Difficulties predicting time-to-arrival in individuals with autism spectrum disorders - Sheppard, Elizabeth; Loon, Editha van; Underwood, Geoffrey; Ropar, Danielle (Elsevier, 2016)
Background: Previous research suggests people with ASD may have various difficulties in processing and interacting with motion in the environment. We investigated whether individuals with ASD have difficulty judging the location of moving objects in a driving context using a time-to-arrival task. Methods